Blockchain Technology in Waste Management: Theoretical Evaluation for System Adoption - Setiawan; Agus Dana Permana; Heri Rahman (Indonesian Journal of Environmental Management and Sustainability, 2022)
In recent years Blockchain technology has become increasingly important and accepted (i.e business sector, supply chain, and other aspects of sustainability). The purpose of this study was to determine the potential of Brewer spent yeast and determine the possibility of blockchain adoption in Brewer Spent Yeast (BSY) waste management. This study uses primary data and literature studies in the preparation of blockchain-based waste management. The data obtained were analyzed using the Decision-Making Trial and Evaluation Laboratory (DEMATEL) method to extract the relationship between criteria within the blockchain framework. From the results of this study, it is known in the blockchain management aspect, it was found that the availability of technology and understanding of technology use insights were the most dominant cause criteria (Ri–Ci)>0.00. While the impact criteria with a value (Ri-Ci)<0.00 such as the criteria can be used for many sources of waste, cheaper transactions, and aspects of a culture of transparency in the implementation of waste treatment. The cause criteria will influence the effect criteria in the process of adopting the blockchain model in Brewer Spent Yeast (BSY) waste management.